Ventricular Premature Beats in Triathletes: Still a Physiological Phenomenon? - Claessens, P.; Claessens, C.; Claessens, M.; Bloemen, H.; Verbanck, M.; Fagard, R. (Cardiology, 2000)
Sudden death is a tragic fact, unexpectedly arising in all age groups. Ventricular arrhythmias are the main cause. At the end of a maximal exercise test more ventricular premature beats were noted in a group of well trained triathletes compared with a similar control group. The etiology is multifactorial. When these ventricular premature beats are associated with specific structural and functional heart adaptations, echocardiographically and electrocardiographically well-documented, then those 'banal' ventricular premature beats cannot longer be considered as a physiological phenomenon. In these circumstances the involved subject is a candidate for dangerous arrhythmias and 'sudden cardiac death'. Purpose: The principal cause of 'Sudden cardiac death' is ventricular arrhythmias. We explore the incidence of ventricular premature beats (VPB) in triathletes, who engage in enforced endurance sports. Methods: Fifty-two triathletes were compared with twenty-two control subjects with comparable anthropometric parameters in function of structural and functional cardiac adaptations. Maximal exercise tests were conducted on a stationary bicycle and a treadmill. During the last two minutes of each test, the VPB were registered. Results: Statistically significant differences emerged in the cardiac structure and function between the triathletes and the controls. There were signs of cardiac hypertrophy and arguments for a supernormally diastolic left ventricular function in the triathletes. The performance capacity was also significantly higher in the triathletes. The maximal heart rate was significantly higher in the control group. The number of VPB was significantly higher in the triathletes. The increased risk of VPB in the triathlon group is caused by several factors: the degree of cardiac hypertrophy, the increased diastolic reserve, the duration of the exercise, the existence of an aortic insufficiency jet and some specific electrocardiographic findings. Conclusions: The triathlete has an increased risk of VPB during maximal efforts. We doubt the traditionally accepted view of the physiological nature of those VPB and suspect that the limit of physiological cardiac adaptations to sport efforts is exceeded with the appearance of VPB. The triathlete with VPB and with specific electrocardiographic and echocardiographic findings is a candidate for 'sudden cardiac death'. Copyright 2000 S. Karger AG, Basel